2012
DOI: 10.1016/j.vaccine.2011.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity against mouse upper genital tract pathology correlates with high IFNγ but low IL-17 T cell and anti-secretion protein antibody responses induced by replicating chlamydial organisms in the airway

Abstract: To search for optimal immunization conditions for inducing protective immunity against upper genital tract pathologies caused by chlamydial intravaginal infection, we compared protection efficacy in mice immunized intranasally or intramuscularly with live or inactivated C. muridarum organisms. Mice immunized intranasally with live organisms developed strong protection against both vaginal shedding of infectious organisms and upper genital tract pathologies. The protection correlated with a robust antigen-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 74 publications
(97 reference statements)
4
56
0
Order By: Relevance
“…[8] However,Lu et al have shown that defense from genital infection by means of live Chlamydia immunization correlates with Т-cell response and is characterized by IFNγ high level and IL-17 low level. [9] Andrew et al in their investigation have illustrated that, in IL-17 absence, clinical gravity in chlamydial genital lesions is considerably lessened; [10] like this, in our study, IL-17 level in the chlamydial infection group was not different from the control values.…”
Section: Discussionsupporting
confidence: 81%
“…[8] However,Lu et al have shown that defense from genital infection by means of live Chlamydia immunization correlates with Т-cell response and is characterized by IFNγ high level and IL-17 low level. [9] Andrew et al in their investigation have illustrated that, in IL-17 absence, clinical gravity in chlamydial genital lesions is considerably lessened; [10] like this, in our study, IL-17 level in the chlamydial infection group was not different from the control values.…”
Section: Discussionsupporting
confidence: 81%
“…Each mouse was inoculated intravaginally with 2 ϫ 10 5 inclusion-forming units (IFU) of live C. muridarum plasmid-competent Nigg or plasmid-free CMUT3 organisms in 20 l of SPG (sucrose-phosphate-glutamate buffer) or intrabursally with different amounts of organisms, as indicated, in 10 l of SPG. For some experiments, plasmid-competent C. muridarum organisms were UV inactivated as described previously (17,18) before inoculation. Five days prior to infection, each mouse was injected subcutaneously with 2.5 mg Depo-Provera (Pharmacia Upjohn, Kalamazoo, MI) to synchronize the estrus cycle and increase mouse susceptibility to chlamydial infection.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is necessary to characterize the C. muridarum-induced uterine horn dilation. Many previous mouse model-based studies grouped both hydrosalpinx and uterine horn dilation as upper genital tract pathology (19,20) and focused only on the fertility outcome (21)(22)(23) or patency of the upper genital tract (6) without differentiating uterine horn dilation from hydrosalpinx (8,(24)(25)(26)(27)(28). Although a previous study reported that interferon regulatory transcription factor 3 (IRF3) protected mice from uterine horn pathology during C. muridarum infection (13) and efforts have also been made to define host factors involved in C. muridarum induction of uterine horn dilation (29), the pathological basis of uterine horn dilation remains unclear.…”
mentioning
confidence: 99%